2014
DOI: 10.1007/s00425-014-2142-y
|View full text |Cite
|
Sign up to set email alerts
|

Overgrowth of Douglas fir (Pseudotsuga menziesii Franco) stumps with regenerative tissue as an example of cell ordering and tissue reorganization

Abstract: Main conclusionStump overgrowth may serve as a unique model for studying cellular reorganization and mechanisms responsible for cell polarity changes during the process of vascular tissue differentiation from initially unorganized parenchymatous cells.Cellular ordering and tissue reorganization during the overgrowth process of the transverse surfaces of Douglas fir stumps in forest stand was studied. At the beginning of stump overgrowth, the produced parenchymatous cells form an unorganized tissue. Particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Malformation and disorganization of tracheids in woundwood, as well as the later recovery of a normal pattern has been recently described in fire scars in different conifers [ 22 ] or in mechanical injuries in the stem of Pinus sylvestris [ 42 ] or even in overgrown stumps of felled Pseudotsuga menziensii [ 60 ]. This disorganized xylem, with an increased proportion of resin ducts and associated parenchyma imply an evident disadvantage for the circulation of water and nutrients through the traumatic xylem [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Malformation and disorganization of tracheids in woundwood, as well as the later recovery of a normal pattern has been recently described in fire scars in different conifers [ 22 ] or in mechanical injuries in the stem of Pinus sylvestris [ 42 ] or even in overgrown stumps of felled Pseudotsuga menziensii [ 60 ]. This disorganized xylem, with an increased proportion of resin ducts and associated parenchyma imply an evident disadvantage for the circulation of water and nutrients through the traumatic xylem [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been shown that this technique may be useful for the evaluation of cellular pattern ordering during morphogenetic processes in plants. the method was successfully applied to pattern analysis and cellular ordering in the area where tissues were regenerating after longitudinal stem wounding of adult Scots pine trees (Zajączkowska 2014a) and during the overgrowth process of transverse surfaces of Douglas fir stumps (Zajączkowska 2014b).…”
mentioning
confidence: 99%
“…In these regions, also tangential resin ducts are developed, perpendicular both to axial and radial canals. Malformation and disorganization of tracheids in woundwood, as well as the later recovery of a normal pattern has been recently described in beetle and fire scars in different conifers (Arbellay et al 2014(Arbellay et al , 2017 or in mechanical injuries in the stem of Pinus sylvestris (Zajaczkowska 2014a) or even in overgrown stumps of felled Pseudotsuga menziensii (Zajaczkowska 2014b).…”
Section: Anatomical Analysis Of Healingmentioning
confidence: 93%
“…Traumatic wood usually presents malformed tracheary elements and fibers, with altered lignification patterns, and with a high proportion of parenchymatic cells. Orientation of these elements is also very often distorted (Zajaczkowska 2014a, 2014b, Arbellay et al 2014, Chano et al 2015, probably due to altered hormonal flux, and also to altered mechanical signals, as suggested in Chapter 2 (Chano et al 2015). This disorganized xylem implies an evident disadvantage for water and nutrient transport (Arbellay et al 2014).…”
Section: Orientation Of Healing Tissuesmentioning
confidence: 99%
See 1 more Smart Citation